2022
DOI: 10.3390/ijms23073492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Umbelliferone on the Anticonvulsant and Neuroprotective Activity of Selected Antiepileptic Drugs: An In Vivo and In Vitro Study

Abstract: Umbelliferone (7-hydroxycoumarin; UMB) is a coumarin with many biological properties, including antiepileptic activity. This study evaluated the effect of UMB on the ability of classical and novel antiepileptic drugs (e.g., lacosamide (LCM), levetiracetam (LEV), phenobarbital (PB) and valproate (VPA)) to prevent seizures evoked by the 6-Hz corneal-stimulation-induced seizure model. The study also evaluated the influence of this coumarin on the neuroprotective properties of these drugs in two in vitro models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…P83 Umbelliferone (Zagaja et al, 2022) and P111 Neohesperidin (Chakraborty et al, 2021) have been reported to exhibit neuroprotective effects. P136 Liquiritigenin (Liu et al, 2022), P116 Tenuifoliside A (Dong et al, 2014), P73 Polygalaxanthone III (Du et al, 2022), P53 Loganin (Pan et al, 2021) and P151 Natsudaidain 3-(4-O-3-Hydroxy-3-Methylglutaroylglucoside) (Okuyama et al, 2017) have been shown to exert their effects through various mechanisms, including changes in neurotransmitter levels, increased cAMP levels and amelioration of locomotor hyperactivity…”
Section: Discussionmentioning
confidence: 99%
“…P83 Umbelliferone (Zagaja et al, 2022) and P111 Neohesperidin (Chakraborty et al, 2021) have been reported to exhibit neuroprotective effects. P136 Liquiritigenin (Liu et al, 2022), P116 Tenuifoliside A (Dong et al, 2014), P73 Polygalaxanthone III (Du et al, 2022), P53 Loganin (Pan et al, 2021) and P151 Natsudaidain 3-(4-O-3-Hydroxy-3-Methylglutaroylglucoside) (Okuyama et al, 2017) have been shown to exert their effects through various mechanisms, including changes in neurotransmitter levels, increased cAMP levels and amelioration of locomotor hyperactivity…”
Section: Discussionmentioning
confidence: 99%
“…The animals were administered with increasing doses of KA-228 and KA-232, and the anticonvulsant activity of each drug was evaluated as the ED 50 . This experimental procedure has been described in detail in our previous studies [19,35].…”
Section: -Hz (32 Ma) Seizure Modelmentioning
confidence: 99%
“…The results for KA-11 were used from Kaminski et al[6]; see compound 11. ED 50 and TD 50 of valproic acid (VPA) were used from Zagaja et al[8,19] and Kaminski et al[20].…”
mentioning
confidence: 99%
“…Coumarins are phenolic compounds produced in plants as secondary metabolites. Most known coumarins include coumarin, umbelliferone, scopoletin and esculetin and have several interesting biological activities, including anti-inflammatory, anticancer, neuroprotective, antifungal, antibacterial, antidiabetic, antiepileptic, cardiovascular protective, antiulcerogenic, and antidiarrheal, among others [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. For example, several coumarins have been studied in clinical trials and demonstrated potential in the treatment of leukemia, renal, and prostate cancers, among others [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%